HOW THE THERAPIST’S COVERT RESPONSES CAN HINDER OR AID CLINICAL CASE MANAGEMENT (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Should the feelings and thoughts that clients evoke in psychotherapists during the session be considered? The purpose of this text is to elucidate the usefulness of observing the psychotherapist's covert responses. This topic is addressed in this conceptual didactic article based on clinical experience and pertinent literature. Three ways of using the covert behaviors are presented and illustrated. The feelings and thoughts elicited and evoked by clients in the therapist, can clarify the client’s interpersonal and social difficulties. Understanding the variables that control these therapist responses can help the decision making that guides treatment. Covert therapist responses can also pinpoint difficulties of the therapist, that can be overcome to enable new directions for treatment. Finally, sharing the therapist’s feelings with the client can benefit the treatment process. To work with his or her private events in practice can be a challenging to the therapist, demanding a discriminative repertoire that is both rule-governed (theoretical understanding) and contingency shaped (resulting from experiential training).